A Study of Hospitality Internship in Gokarna Forest Resort, Nepal - Kunwar, Ramesh Raj; Khatri-Thapa, Sarswati (Journal of Tourism and Hospitality Education, 2016)
Hospitality and Tourism industry and internship are crucial to each other and for this reason, the industry as well as the prospective intern should be fully aware about the internship and its various aspects. To make the internship more effective it should be studied from the perspective of prospective interns and the employer. Because of the lack of adequate understanding the interns as well as the employers are facing the difficulties when the internship starts. This article tries to present an internship from various perspectives as well as portray an intern’s change of understanding about the internship before and after the involvement in the field. This portray mainly focus on the concept of internship, knowledge before, during and after internship, learning experience, difference between theoretical and real life world with some suggestions for the following generations. Journal of Tourism and Hospitality Education (Vol. 6), 2016, Page: 95-126